PENGARUH PERSONAL SELLING TERHADAP KEPUTUSAN PEMBELIAN DI PT. F C C NESTLE CIMAHI - wiwi warsiati; Damianus Daeli (EKBIS (Ekonomi & Bisnis), 2022)
Abtract This research was conducted to avoid the large influence of personal selling influence on purchasing decisions, which can be relied upon in personal interventions and to measure what the company is doing in overcoming the problem of personal selling of PT. F C C NESTLE Cimahi Branch. The research method used is quantitative research methods, data collection methods used are questionnaires, observation and literature study. The sample used was 72 respondents from the results of the study population. The analysis technique used is the product analysis technique when processing data using SPSS 25. The results showed that there was an effect of personal selling on the purchasing decision of PT. F C C NESTLE Cimahi, at 68.1%, indicating a strong relationship. The results of the calculation of the coefficient of determination of 46.4% are seen in R Sguare and the remaining 53.6% from other factors not examined by the author, this shows that the effect of personal selling on purchasing decisions. To improve purchasing decisions of prospective customers through personal selling, it is necessary to increase human resources, provide motivation and appreciation for employees, choose a good promotion time and must master the company's products. Keywords: Personal Selling, Purchasing Decisions